Cinderella 2 : dreams come true. (Pasig City : Viva Video, 2002)
The magical story of Cinderella continues in an all-new full-length movie brimming with irresistible music, lush animation and all your favorite characters from the original Disney classic. When Cinderella and her prince return to the palace from their honeymoon, the new princess suddenly finds herself cast in the role of Royal Hostess. With the help of everyone's favorite Fairy Godmother and a band of mischievous mice, Cinderella and her friends find that the only true way to succeed is to be yourself. You'll find dreams really do come true in the enchanting tale of CINDERELLA II: DREAMS COME TRUE.